A review of III-V Tunnel Field Effect Transistors for future ultra low power digital/analog applications. (August 2021) - Saravanan, M.; Parthasarathy, Eswaran
Abstract: Tunnel Field Effect Transistors (TFETs) have emerged as serious contenders for the replacement of traditional MOSFET technology for the future ultra low power Analog/Digital circuit applications because of their unique properties such as Sub-60 mV/decade subthreshold swing (SS), negligible short channel effects (SCEs) and very low off current (IOFF ). This review article intensively studies the RF/Analog and DC performance of III-V materials based TFETs. This article highlights the scalability of III-V TFETs, influence of thickness and permittivity of gate dielectric, interface trap density, other geometrical dimensions, material properties and various TFET architectures on the ON and OFF state performance of III-V TFETs. This paper also point outs the impact of temperature, strain, gate metal work function, source-gate overlap and underlap, doping concentration and supply voltage scaling on the DC, RF/Analog characteristics of III-V TFETs.